2011
DOI: 10.4103/1319-3767.74461
|View full text |Cite
|
Sign up to set email alerts
|

Non-association of IL-12 +1188 and IFN-γ +874 polymorphisms with cytokines serum level in occult HBV infected patients

Abstract: Background/Aim:Occult hepatitis B infection (OBI) is identified as a form of hepatitis in which despite the absence of detectable HBsAg, HBV-DNA is observed in peripheral blood of patients. The main aim of this study has been to investigate the association between polymorphisms in +874 of IFN-γ and +1188 of IL-12 with their serum level in patients suffering from OBI.Materials and Methods:In this experimental study, plasma samples of 3700 blood donors were tested for the presence of hepatitis B surface antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 11 publications
4
43
0
Order By: Relevance
“…The majority of post transfusion hepatitis B infections are caused by OBI [4], which we previously reported in our investigations in Isfahan [5] and Kerman [4], the two main central provinces of Iran. The mechanisms responsible for progression of OBI are yet to be clarified; however, some investigators have suggested that genetic and immunological parameters may play a significant role in the resistance of some individuals and sensitivity of others [4,6,7]. The key roles of IL-10 as an inhibitory cytokine of autoimmune and inflammatory reactions [8] raise questions concerning the impacts of this cytokine in the pathogenesis of OBI.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The majority of post transfusion hepatitis B infections are caused by OBI [4], which we previously reported in our investigations in Isfahan [5] and Kerman [4], the two main central provinces of Iran. The mechanisms responsible for progression of OBI are yet to be clarified; however, some investigators have suggested that genetic and immunological parameters may play a significant role in the resistance of some individuals and sensitivity of others [4,6,7]. The key roles of IL-10 as an inhibitory cytokine of autoimmune and inflammatory reactions [8] raise questions concerning the impacts of this cytokine in the pathogenesis of OBI.…”
Section: Introductionmentioning
confidence: 55%
“…Despite the application of programs for appropriate screening of all donated blood and blood components for HBsAg, some cases of posttransfusion hepatitis B are reported worldwide [3]. The majority of post transfusion hepatitis B infections are caused by OBI [4], which we previously reported in our investigations in Isfahan [5] and Kerman [4], the two main central provinces of Iran. The mechanisms responsible for progression of OBI are yet to be clarified; however, some investigators have suggested that genetic and immunological parameters may play a significant role in the resistance of some individuals and sensitivity of others [4,6,7].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Some studies reported that patients who carry the IL-12 -1188 C allele are low IL-12 producers, while other studies found no evidence of the polymorphism effect on cytokine expression [41,42]. The IL-12 -1188 C allele or CC genotype has been associated with inflammatory and infectious diseases such as asthma [43], tuberculosis [44], leprosy [41], subacute sclerosing panencephalitis [45], and occult hepatitis B infection [42]; on the other hand, the AA genotype confers an increased risk of psoriatic arthritis [46] and multiple sclerosis [47]. IL2/IL21 and IL12B have been identified in genome-wide association studies to be associated with CD and UC [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…While Morahan et al demonstrated that this polymorphism was associated with a decreased IL-12B mRNA expression by EBV transformed cell lines [25]. Arababadi et al suggested that the polymorphisms in 1188 region of IL-12 and +874 region of IFN-γ would not affect the expression of both cytokines at a serum level in Occult HBV Infected Patients [26]. In addition, previous research provided several reports about the association between the polymorphism of IL-12A with HBV infection.…”
Section: Discussionmentioning
confidence: 99%